A Model of Legal Protection for Justice Collaborators and Whistleblowers in Corruption Crimes - Rahmat, Doni; Hakim, Lukman; Zulfikar Putra Prawiranegara, Muhammad (Fakultas Hukum, Universitas Islam Balitar, 2024)
This article focuses on analyzing and developing the legal protection concept for justice collaborators and whistleblowers in corruption cases. The urgency of this research lies in the fact that protection for these key figures in crime disclosure remains insufficient. The study identifies legal gaps in the current regulations concerning their protection. Employing statutory, conceptual, and comparative legal approaches, the research reveals that the existing framework for justice collaborators and whistleblowers still faces legal challenges. The findings recommend a more comprehensive protection system, not only during legal proceedings but also after the sentencing. Rewards for their cooperation could include immunity from prosecution or lighter penalties, such as probationary sentencing. The implications of this study highlight the necessity for regulatory reform to enhance legal protection for both justice collaborators and whistleblowers.